Chemical Capture of a Problem - Elephant in Bolangir, Orissa - Singh, L. A. K.; Nayak, B. N.; Acharjya, S. K. (Indian Forester, 1996)
The paper presents the results of operations launched to capture the Elephant using chemicals ia Bolangir.